2001
DOI: 10.1054/bjoc.2001.2096
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk of cancer in middle-aged men

Abstract: Summary A prospective study was carried out to examine the relationship between physical activity and incidence of cancers in 7588 men aged 40-59 years with full data on physical activity and without cancer at screening. Physical activity at screening was classified as none/occasional, light, moderate, moderately-vigorous or vigorous. Cancer incidence data were obtained from death certificates, the national Cancer Registration Scheme and self-reporting on follow-up questionnaires of doctor-diagnosed cancer. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(177 citation statements)
references
References 33 publications
3
170
1
3
Order By: Relevance
“…From 422 unique studies identified using the search strategy, 15 studies met the inclusion criteria (13)(14)(15)(16)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). One population-based case-control study by Campbell and colleagues, using the Canadian National Enhanced Cancer Surveillance Study, reported and analyzed data from Ontario and seven other Canadian provinces separately using different physical activity measurement modality, and hence, these were analyzed as two separate studies (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 422 unique studies identified using the search strategy, 15 studies met the inclusion criteria (13)(14)(15)(16)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). One population-based case-control study by Campbell and colleagues, using the Canadian National Enhanced Cancer Surveillance Study, reported and analyzed data from Ontario and seven other Canadian provinces separately using different physical activity measurement modality, and hence, these were analyzed as two separate studies (25).…”
Section: Resultsmentioning
confidence: 99%
“…The earliest cohort study recruited patients starting in 1965 and latest completed recruitment in 2000, with mean reported follow-up ranging from 6 to 18.8 years (13,14,16,29,30,32,33). Five studies were performed in Asian populations (16,26,27,31,32) and 10 studies were performed in Western populations (six in North America; refs.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…[1][2][3][4][5] A Western lifestyle is also associated with insulin resistance, which in turn has been linked to higher prostate cancer risk. 6 Dietary carbohydrates have different potentials to raise blood glucose and insulin levels and, hence, to modulate insulin sensitivity.…”
mentioning
confidence: 99%
“…More than half the studies in this area show an inverse relationship between physical activity and PC, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] other studies show no association [31][32][33][34][35][36][37][38][39][40][41][42] and four studies even found exercise increased PC risk. [43][44][45][46] Perhaps this uncertainty in the literature can be attributed to the epidemiological nature of the research designs utilized in these studies, which relied upon survey or patient self-reporting to elicit physical activity and/or exercise exposure.…”
Section: Exercise and Prostate Cancer Preventionmentioning
confidence: 99%